A reasonable defense - Kaufmann, William W. (Washington, D.C. : Brookings Institution, 1986)
The views expressed in this study are those of the author's. He concentrates on assessing how three different U.S. force structures would respond to a number of standard planning contingencies. He also compares the relative effectiveness of these force structures in countering a Soviet first strike with strategic nuclear forces and a non-nuclear invasion of Central Europe by the Warsaw Pact.
Includes bibliographical references.
ne 12/06/2018
Loans
Keywords: Budget; United States